Effect of cargo size and shape on the transport efficiency of the bacterial Tat translocase. Issue 7 (16th February 2013) - Whitaker, Neal; Bageshwar, Umesh; Musser, Siegfried M.
Abstract : The Tat machinery translocates fully‐folded and oligomeric substrates. The passage of large, bulky cargos across an ion‐tight membrane suggests the need to match pore and cargo size, and therefore that Tat transport efficiency may depend on both cargo size and shape. A series of cargos of different sizes and shapes were generated using the natural Tat substrate pre‐SufI as a base. Four (of 17) cargos transported with significant (>20% of wild‐type) efficiencies. These results indicate that cargo size and shape significantly influence Tat transportability. Abstract : ► Seventeen modified pre‐SufI cargos were tested for Tat translocation. ► Cargo size and shape significantly influenced Tat transport efficiency. ► Smaller cargos transported more efficiently than larger cargos.